THE ROLE OF INTERNET NETWORKS IN THE DAILY LIFE OF ADOLESCENTS - A. Abdullazizov (Journal Park Publishing, 2025)
This article is an attempt to show the role, positive and negative consequences of Internet networks in the daily life of adolescents.
Keywords: Internet, teenagers, Facebook, Instagram, Vkontakte, worldview, ethics and education, videos, films, books.